Field Drainage Investigation - Patil, R.F. (Journal of Soil and Water Conservation, 2022)
If one carefully examines the country side the lands under cultivatioi in a water will very often fiel a portion of the area on the lowar side of the valley having gone out of cultivation due to the concentration or salts at the surface which are injurious to the growth of crops. In most vises the owners of these lands have become helpless victims or unproductive lands. Ia some of the districts like Bijapur thousands of hectares of good cultivated land have become barren wastes owing to such concentration of salts and the farmers are clamouring for the improvement of these lands so that they become productive again. Excess soluble salts and alkali and drought cause sterility. Saline and alkali lands are characteristic of arid regions. Saline soils have excess soluble salts which render them unproductive. Alkali soils have an excess of exchangeable sodium with or without execssive total soluble salts.